Effectiveness of Cadre Capacity Building Activities: a Comparative Design - Nurul Hayati; Sri Wahyuningsih; R. Endro Sulistyono; Primasari Mahardika Rahmawati (Universitas Jember, 2022)
Immunization is a form of health intervention that is very effective in reducing infant and under-five mortality. However, until now the implementation has not reached the maximum target, there are still many people who do not allow their children to be immunized for various reasons. Ignorance of the community or parents about the importance of immunization is one of the main causes, therefore the role of posyandu cadres is needed. One of the roles of posyandu cadres is to provide health education to the community or parents about immunization, so that capacity building activities for cadres are very necessary to increase the knowledge of posyandu cadres. The purpose of this study was to analyze the knowledge and abilities of cadres in an effort to increase the coverage and quality of immunization in Ranupakis Village, Klakah District. The research method was carried out in stages starting from FGD (Focus Group Discussion) activities, pre-test activities to determine the level of knowledge of cadres, health education activities about immunization, and post-test activities. The results of the activity showed that there was a significant influence on the knowledge and abilities of cadres regarding imusization. The conclusion of this study proves that the increased knowledge and ability of cadres has an effect on their role in the coverage and quality of immunization. Keywords: immunization coverage; the role of cadres